Experience with Evans syndrome in an academic referral center - Jaime Pérez, José Carlos; Guerra Leal, Liliana Nataly; López Razo, Olga Nidia; Méndez Ramírez, Nereida; Gómez Almaguer, David (2015)
Objective: To document the experience of one referral service with patients diagnosed with Evans syndrome, the treatment and response and to briefly review current treatment strategies and results. Methods: Patients enrolled in this study fulfilled criteria for Evans syndrome. Data were retrieved from the clinical files and electronic databases of the Department of Hematology, Hospital Universitario “Dr. José Eleuterio González”. Treatment modalities and response and the use of additional therapies were evaluated. The literature was reviewed in the context of the clinical course of the studied patients. Results: Six patients were diagnosed with Evans syndrome in the study period. Patient 1 was treated with steroids, relapsed twice and was again treated with steroids. Patient 2 treated initially with steroids plus intravenous immunoglobulin was subsequently lost to follow-up. A good response was achieved in Patients 3 and 4, who were treated with steroids plus rituximab; patient 4 also received danazol as a second-line therapy. However both relapsed and subsequently underwent splenectomy at ten and nine months, respectively. One patient, number 5, treated with steroids, danazol and rituximab did not relapse within four years of follow-up and Patient 6, who received steroids plus danazol did not relapse within three years of follow-up. Conclusion: Evans syndrome is an uncommon hematologic condition rarely diagnosed and not widely studied. Clinicians must have itin mind when evaluating a patient with a positive direct antiglobulin test, anemia and thrombocytopenia, since prognosis depends on its early recognition and opportune therapy, but even this leads to variable results.